2021
DOI: 10.1183/20734735.0037-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measuring adherence to therapy in airways disease

Abstract: Non-adherence to medication is one of the most significant issues in all airways disease and can have a major impact on disease control as well as on unscheduled healthcare utilisation. It is vital that clinicians can accurately determine a patient's level of adherence in order to ensure they are gaining the maximal benefit from their therapy and also to avoid any potential for unnecessary increases in therapy. It is essential that measurements of adherence are interpreted alongside biomarkers of mechanistic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…This method can detect non-adherence by identifying previously non-respondents that respond well to an EMD-monitored high-dose ICS therapy, compared with non-respondents, despite the adequate level of adherence (ICS resistant) who may require alternative treatments such as escalation to biologic therapy 29. Owing to improved adherence to ICS and consequent improvement in asthma control, the FeNO suppression test led to significantly fewer patients with uncontrolled asthma progressing to biologic therapy 8. Although EMDs improve adherence, the associated costs of using EMDs with extra/fewer resources allocated by more/less GP/pharmacist/nurse visits for data collection and interpretation need to be considered 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method can detect non-adherence by identifying previously non-respondents that respond well to an EMD-monitored high-dose ICS therapy, compared with non-respondents, despite the adequate level of adherence (ICS resistant) who may require alternative treatments such as escalation to biologic therapy 29. Owing to improved adherence to ICS and consequent improvement in asthma control, the FeNO suppression test led to significantly fewer patients with uncontrolled asthma progressing to biologic therapy 8. Although EMDs improve adherence, the associated costs of using EMDs with extra/fewer resources allocated by more/less GP/pharmacist/nurse visits for data collection and interpretation need to be considered 30.…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence to regular inhaled corticosteroids (ICS) alone or in combination with a long-acting β2-agonist (LABA) contributes to 34% of asthma deaths in the United Kingdom 7. Treatment adherence can be monitored subjectively using validated questionnaires, or objectively by using different methods, including drug dose counting, prescription possession ratios and measuring drug levels in the blood or urine 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Severe Asthma Network in Italy stated in a 2020 publication that ''considering the strong impact that frequent or regular use of OCS has on [the quality of life] of severe asthmatics, as well as the costs for managing corticosteroid-related disease, OCSsparing up to withdrawal should be considered a primary outcome in the management of severe asthma'' [52]. To address the overreliance on OCS, we have identified the following key headline actions, and a series of proposed measures, to address the barriers to change in OCS use (Table 2) [51,[53][54][55][56]. Previous research has shown that avoidable risk factors contribute to premature death and suggest that past history is sometimes expected and/or accepted [57,58].…”
Section: Steps To Implement Changes Worldwidementioning
confidence: 99%
“…Patients should receive an asthma review when an alert flags them as having an ICS autorefill of less than 80% per year [53,56,75]. This alert may be from primary care (the prescriber) or a pharmacist (the dispenser).…”
Section: Recommendationmentioning
confidence: 99%